Aprendendo a ser professor: caminhos da formação no início da carreira docente em Geografia - Alessandra Bernardes Faria Campos (2013)
Learning how to teach is a common aspect that academic works on beginning teachers discuss. However, this subject still needs deeper analysis and a discussion that takes into consideration teachers working conditions. In this research, I discuss the process of becoming a Geography teacher. Data have been gotten through both questionnaires and interviews with nine beginning teachers all of them had at most six years of teaching experience and came from two private and one public universities, teaching at different levels at Belo Horizonte school district. Two main research lines have been used during this research: (1) aspects related to live history, schooling, and teacher training; (2) contextual issues related to teachers working conditions. It has been possible through this research to realize the relationship between the ways to think about teaching, and more specifically about teaching Geography, the school, and young teachers professional learning. In addition, it is clear that the students play an important role during this process of learning how to teach. Other issues are more related to the teachers working conditions like the way they are welcomed into the school and the teaching profession itself, whether or not they are able to do their work with autonomy and creativity or if they only have to adapt themselves to the school structures, function and organization.